Nashville Cats Record Production in Music City - Stimeling, Travis D. (Oxford University Press, Incorporated, 2020)
Nashville Cats: Record Production in Music City, 1945-1975 explores the roles that recording engineers, session musicians, and record producers played in shaping the sounds of country music during the fertile "Nashville Sound" era